2015
DOI: 10.1016/j.abb.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

A novel vasorelaxant lectin purified from seeds of Clathrotropis nitida : partial characterization and immobilization in chitosan beads

Abstract: A novel lectin from seeds of Clathrotropis nitida (CNA) was purified and characterized. CNA is a glycoprotein containing approximately 3.3% carbohydrates in its structure. CNA promoted intense agglutination of rabbit erythrocytes, which was inhibited by galactosides and porcine stomach mucin (PSM). The lectin maintained its hemagglutinating activity after incubation in a wide range of temperatures (30-60 °C) and pH (6.0-7.0), and its binding activity was dependent on divalent cations (Ca(+2) and Mg(+2)). SDS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…Purified lectin was found to be a glycoprotein as determined by PAS staining whereas carbohydrate content of lectin was observed up to 5.2%. Similar carbohydrate contents of lectin have been reported in case of lectin purified from Artocarpus integerifolia and Clathrotropis nitida [34] Hemagglutination activity of hyacinth lectin was inhibited by mannose and ovalbumin which suggested that its manose binding lectin which is one of the significant properties of lectin purified from monocotyledon plants. Hyacinth lectin showed moderate temperature and pH stability.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Purified lectin was found to be a glycoprotein as determined by PAS staining whereas carbohydrate content of lectin was observed up to 5.2%. Similar carbohydrate contents of lectin have been reported in case of lectin purified from Artocarpus integerifolia and Clathrotropis nitida [34] Hemagglutination activity of hyacinth lectin was inhibited by mannose and ovalbumin which suggested that its manose binding lectin which is one of the significant properties of lectin purified from monocotyledon plants. Hyacinth lectin showed moderate temperature and pH stability.…”
Section: Discussionsupporting
confidence: 79%
“…Carbohydrate content and glycosylation nature of Hyacinth bulb lectin was determined by anthrone assay and PAS staining respec- tively. The carbohydrate content of purified lectin was found to be 5.2% and according to literature carbohydrate content of lectin vary from 1.5 to 16% [33,34]. PAS stain result indicated that hyacinth lectin was glycoprotein in nature ( Fig.…”
Section: Carbohydrate Content and Glycosylation Nature Of Hyacinth Lementioning
confidence: 60%
“…The lectin proved to be thermostable with maximum activity at temperatures of 30 ºC, 40 ºC and 50 ºC, but its activity was reduced when 100 ºC was reached. Other lectins of the same botanical family show maximum activity at similar temperatures, such as the Collaea speciosa lectin isolated by Oliveira et al (2021) and the lectin isolated by Alves et al (2015) from seeds of Clathrotropis nitida, which showed low hemagglutinating activity at 100 ºC. Total dependence of CiL on divalent ions, as noted above, closely resembled the findings of Pinto-Junior et al (2016) who isolated a metal-dependent lectin from the seeds of Dioclea reflexa.…”
Section: Physicochemical Characterizationsupporting
confidence: 71%